MUTU PENDIDIKAN PADA PERGURUAN TINGGI KEAGAMAA: Dari Manajemen Kelembagaan Hingga Konstruksi Kurikulum Interrelasi - Elbadiansyah, Dakir (MUADDIB Jurnal Kependidikan dan Keislaman, 2017)
The development of the quality of religious universities in general is still left behind. One of the causes, construction of the foundation of quality in religious colleges is still partial. This article attempts to identify the quality of general religious college education in Indonesia through critical analysis and offers alternative solutions to improve it. One of the right models to improve the quality of education is the global quality assurance model. This model is an integration of PD Dikti quality standards, quality standards of National Accreditation Board, internal quality audit, Webometric, and religious institutions distingsi standards. As for improving the quality of education and learning of lecturers and students are able to produce learning products in the form of books and scientific articles published in national and international scientific journals as well as increasing the competence of graduates. Therefore the aspects of ontology, epistemology and axiology in the integration of science in the curriculum of education need to be constructed with critical interrelation model. This model is relatively effective enough to anticipate the occurrence of pseudo interconnects, preventing hybridity and new hegemonic scholarship in the pattern of interconnectivity and protect the characteristics of every science.